A Victimological Review of Fraud Committed by Online Motorcycle Taxi Drivers Against Consumers - Muhammad Gading Bintang Hadhani; Kayus Kayowuan Lewoleba (Jurnal Daulat Hukum, 2026)
The advancement of information technology during the fourth Industrial Revolution has led to the emergence of an app-based transportation services that offer efficiency and convenience for the society. However, alongside these advancements, new forms of crime have also emerged, including online motorcycle taxi drivers' fraud against customers. In addition to examining legal protection and the restoration of victims' rights from a victimological perspective, this study attempts to understand the forms and methods of such deception. The study uses statute and case techniques as part of a normative legal method, and the research using primary and secondary legal sources. The findings indicate that fraudulent practices have evolved into complex patterns, ranging from system manipulation such as fake GPS and fictitious orders to deceptive conduct in direct interactions with consumers. Although legal protection is regulated under the Consumer Protection Law, the Electronic Information and Transactions Law, and the Criminal Code, its implementation remains ineffective, particularly regarding evidence and authorities. Furthermore, the recovery of victims’ rights is still limited to material compensation and does not yet reflect a comprehensive victimological approach. Therefore, stronger regulations, greater platform accountability, and more comprehensive victim recovery mechanisms are necessary.